An Evaluation of Heavy Metals Content in Dyeing and Printing Industrial Effluents in GIDC Surat: A Statistical Approach - PATIL, K.L.; SAWANT, C.P. (Asian Journal of Chemistry, 2010)
The present paper reports the heavy metals content in dyeing and printing industrial effluents from Gujarat Industrial Development Corporation (GIDC) area of Surat. The effluent of this area is discharged into rivulet and finally goes to the creek. The metals monitored are Cd, Pb, Fe, Cr, Ni, Zn, Cu, Hg, As, Mn, Se, Sb, Mo. The results are compared with WHO and Indian standards.